Magnetic macroporous bead cellulose functionalised with recombinant hyaluronan lyase for controllable hyaluronan fragmentation - Kašparová, Jitka; Korecká, Lucie; Pepeliaev, Stanislav; Bílková, Zuzana; Smirnou, Dzianis; Velebny, Vladimir; Česlová, Lenka (Elsevier Science, 2018)
Hyaluronic acid (HA) is a component of the extracellular matrix with important potential for biotechnological and pharmaceutical applications. However, the immunological effects of HA are strongly molecular weight-dependent; therefore, production of HA for therapeutic purposes requires control over the molecular weight of the product, as well as mild reaction conditions and elimination of bioactive impurities. Here, we produced and characterised biocompatible magnetic macroporous bead cellulose (MBC) functionalised with Streptococcus pneumoniae hyaluronan lyase (SpnHL) that are compatible with these requirements and optimised their reaction and storage conditions. Immobilisation of SpnHL on MBC via reductive amination or MBC with fixed iminodiacetic acid (MBC-IDA) via a His(8)-tag had minimal impact on its catalytic activity. The MBC-IDA-SpnHL carrier showed excellent operational and storage stability, and both carriers enabled reproducible time-controlled fragmentation of highly viscous HMW HA solutions, yielding HA fragments of appropriate molecular weight. Thus, these carriers are suitable for numerous industrial and biotechnological applications.
Magnetická makroporézní perlová celulóza funkcionalizovaná rekombinantní Hyaluronan lyázou pro kontrolovanou fragmentaci hyaluronanu
Keywords: Hyaluronan; Hyaluronan lyase; Enzyme immobilisation; Magnetic beads; Hyaluronan; Hyaluronan lyáza; Enzymová imobilizace; Magnetické částice